Solution-processed Sr-doped NiOx as hole transport layer for efficient and stable perovskite solar cells. (1st November 2018) - Zhang, Jiankai; Mao, Wujian; Hou, Xian; Duan, Jiaji; Zhou, Jianping; Huang, Sumei; Ou-Yang, Wei; Zhang, Xuehua; Sun, Zhuo; Chen, Xiaohong
Graphical abstract: Highlights: Sr-doped NiOx films were prepared with low annealing temperature of 235 °C. Sr:NiOx based perovskite solar cells (PSCs) got PCE of 20.07%. PSCs based on Sr:NiOx show better stability compared to pure NiOx. Sr:NiOx film shows better conductivity and boosts crystallinity of perovskite layer. Abstract: Nickel oxide (NiOx ) hole transport layer (HTL)-based planar perovskite solar cells (PSCs) have attracted much attention due to high power conversion efficiency (PCE) and simple processing. In this work, smooth and compact Sr-doped NiOx films with different Sr doping concentration were successfully prepared through a simple low temperature sol-gel method. The 1 at.% Sr-doped NiOx HTL-based PSCs exhibited the best performance with PCE of 20.07%, which is greatly higher than PCE of reference NiOx based PSCs (15.73%). Furthermore, the unencapsulated PSCs based on Sr:NiOx HTL still retains over 60% of the original PCE value aging for 100 days under ambient air, showing better stability. The superior performance of Sr-doped NiOx based PSCs is attributed to better electrical conductivity, crystallinity of perovskite film and energy level matching with perovskite layer, which can greatly improve hole transport and extraction abilities and reduce carrier recombination, resulting in high PCE and better stability.